Single dose oral ibuprofen for acute postoperative pain in adults - Derry, C; Derry, S; Moore, R; McQuay, H; Moore, M (2009)
Background: This review updates a 1999 Cochrane review showing that ibuprofen at various doses was effective in postoperative pain in single dose studies designed to demonstrate analgesic efficacy. New studies have since been published. Ibuprofen is one of the most widely used non-steroidal anti-inflammatory (NSAID) analgesics both by prescription and as an over-the-counter medicine. Ibuprofen is used for acute and chronic painful conditions. Objectives: To assess analgesic efficacy of ibuprofen in single oral doses for moderate and severe postoperative pain in adults. Search strategy: We searched Cochrane CENTRAL, MEDLINE, EMBASE and the Oxford Pain Relief Database for studies to May 2009. Selection criteria: Randomised, double blind, placebo-controlled trials of single dose orally administered ibuprofen (any formulation) in adults with moderate to severe acute postoperative pain. Data collection and analysis: Two review authors independently assessed trial quality and extracted data. Pain relief or pain intensity data were extracted and converted into the dichotomous outcome of number of participants with at least 50% pain relief over 4 to 6 hours, from which relative risk and number-needed-to-treat-to-benefit (NNT) were calculated. Numbers of participants using rescue medication over specified time periods, and time to use of rescue medication, were sought as additional measures of efficacy. Information on adverse events and withdrawals were collected. Main results: Seventy-two studies compared ibuprofen and placebo (9186 participants). Studies were predominantly of high reporting quality, and the bulk of the information concerned ibuprofen 200 mg and 400 mg. For at least 50% pain relief compared with placebo the NNT for ibuprofen 200 mg (2690 participants) was 2.7 (2.5 to 3.0) and for ibuprofen 400 mg (6475 participants) it was 2.5 (2.4 to 2.6). The proportion with at least 50% pain relief was 46% with 200 mg and 54% with 400 mg. Remedication within 6 hours was less frequent with higher doses, with 48% remedicating with 200 mg and 42% with 400 mg. The median time to remedication was 4.7 hours with 200 mg and 5.4 hours with 400 mg. Sensitivity analysis indicated that pain model and ibuprofen formulation may both affect the result, with dental impaction models and soluble ibuprofen salts producing better efficacy estimates. Adverse events were uncommon, and not different from placebo. Authors' conclusions: The very substantial amount of high quality evidence demonstrates that ibuprofen is an effective analgesic in treating postoperative pain. NNTs for 200 mg and 400 mg ibuprofen did not change significantly from the previous review even when a substantial amount of new information was added. New information is provided on remedication. Copyright © 2009 The Cochrane Collaboration. Published by John Wiley and Sons, Ltd.